Caste Politics in Bihar: In Historical Continuum. (July 2018) - Ankit, Rakesh
Abstract: This article provides a long-term narrative of movements for social change in Bihar, precipitated by the steady rise to political power by the Backward Classes/Castes in the state, since 1989. Locating this moment in a longer momentum of struggle since the 1920s, it probes the antecedents of recent social change in Bihar politics. Contextualising this process within a long recessional, it traces a larger democratic cycle of empowerment going back to the early twentieth century. The article attempts the historicisation of Bihar politics by drawing upon a variety of sources—from official records to newspapers—and supplementing them with relevant secondary literature.